Purification of a fibrinolytic protease from Mucor subtilissimus UCP 1262 by aqueous two-phase systems (PEG/sulfate) - Nascimento, Thiago Pajeú (2016)
A fibrinolytic protease from M. subtilissimus UCP 1262 was recovered and partially purified by polyethylene glycol (PEG)/sodium sulfate aqueous two-phase systems (ATPS). The simultaneous influence of PEG molar mass, PEG concentration and sulfate concentration on the enzyme recovery was first investigated using a 23 full factorial design, and the Response Surface Methodology used to identify the optimum conditions for enzyme extraction by ATPS. Once the best PEG molar mass for the process had been selected (6000 g/mol), a two-factor central composite rotary design was applied to better evaluate the effects of the other two independent variables. The fibrinolytic enzyme was shown to preferentially partition to the bottom phase with a partition coefficient (K) ranging from 0.2 to 0.7. The best results in terms of enzyme purification were obtained with the system formed by 30.0% (w/w) PEG 6000 g/mol and 13.2% (w/w) sodium sulfate, which ensured a purification factor of 10.0, K of 0.2 and activity yield of 102.0%. SDSPAGE and fibrin zymography showed that the purified protease has a molecular mass of 97 kDa and an apparent isoelectric point of 5.4. When submitted to assays with different substrates and inhibitors, it showed selectivity for succinyl-l-ala-ala-pro-l-phenylalanine-p-nitroanilide and was almost completely inhibited by phenylmethylsulfonyl fluoride, behaving as a chymotrypsin-like protease. At the optimum temperature of 37° C, the enzyme residual activity was 94 and 68% of the initial one after 120 and 150 min of incubation, respectively. This study demonstrated that M. subtilissimus protease has potent fibrinolytic activity compared with similar enzymes produced by solid-state fermentation, therefore it may be used as an agent for the prevention and therapy of thrombosis. Furthermore, it appears to have the advantages of low cost production and simple purification.